Religion im kulturellen Diskurs / Religion in Cultural Discourse: Festschrift für Hans G. Kippenberg zu seinem 65. Geburtstag / Essays in Honor of Hans G. Kippenberg on the Occasion of His 65th Birthday - Luchesi, Brigitte; Stuckrad, Kocku von (Religionsgeschichtliche Versuche und Vorarbeiten, 2004)
Biographical note: Brigitte Luchesi is researcher and lecturer in Religious Studies at the University of Bremen, Germany. Kocku von Stuckrad is researcher and lecturer in Religious Studies at the University of Amsterdam, for the History of Hermetic Philosophy and Related Currents.